Limited Proteolysis-Coupled Mass Spectrometry Identifies Phosphatidylinositol 4,5-Bisphosphate Effectors in Human Nuclear Proteome - Sztacho, Martin; Šalovská, Barbora; Červenka, Jakub; Balaban, Can; Hoboth, Peter; Hozák, Pavel (Cells, 2021)
Specific nuclear sub-compartments that are regions of fundamental processes such as gene expression or DNA repair, contain phosphoinositides (PIPs). PIPs thus potentially represent signals for the localization of specific proteins into different nuclear functional domains. We performed limited proteolysis followed by label-free quantitative mass spectrometry and identified nuclear protein effectors of the most abundant PIP-phosphatidylinositol 4,5-bisphosphate (PIP2). We identified 515 proteins with PIP2-binding capacity of which 191 'exposed' proteins represent a direct PIP2 interactors and 324 'hidden' proteins, where PIP2 binding was increased upon trypsin treatment. Gene ontology analysis revealed that 'exposed' proteins are involved in the gene expression as regulators of Pol II, mRNA splicing, and cell cycle. They localize mainly to non-membrane bound organelles-nuclear speckles and nucleolus and are connected to the actin nucleoskeleton. 'Hidden' proteins are linked to the gene expression, RNA splicing and transport, cell cycle regulation, and response to heat or viral infection. These proteins localize to the nuclear envelope, nuclear pore complex, or chromatin. Bioinformatic analysis of peptides bound in both groups revealed that PIP2-binding motifs are in general hydrophilic. Our data provide an insight into the molecular mechanism of nuclear PIP2 protein interaction and advance the methodology applicable for further studies of PIPs or other protein ligands.
Keywords: Proteolysis; Gene Expression Regulation; Humans; lidé; genová ontologie; Phosphatidylinositol 4,5-Diphosphate; hydrofobní a hydrofilní interakce; proteom; peptidy; Peptides; Hydrophobic and Hydrophilic Interactions; Gene Ontology; hmotnostní spektrometrie; HeLa Cells; proteolýza; Mass Spectrometry; Amino Acid Sequence; sekvence aminokyselin; trypsin; fosfatidylinositol-4,5-difosfát; Trypsin; HeLa buňky; Proteome; regulace genové exprese; Cell Nucleus; buněčné jádro